2016
DOI: 10.1080/08946566.2016.1249816
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualization of mistreatment by older American Indians

Abstract: The problem of how to conceptualize elder mistreatment goes back several decades, and is especially important for ethnic minority populations, who may have perspectives that differ from the dominant society. This community-based participatory research study, which examined perceptions of mistreatment by family among 100 urban and rural older American Indians, permits a rare glimpse into how Native elders themselves understand this issue. Here, good treatment was conceptualized in terms of being taken care of, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Although three studies (31,(33)(34) carried out educational interventions that clarified what is considered violence to elder people and their families, modified and elucidated concepts and typologies, and two of them (31,34) showed results with statistical significance, with all participants in the intervention modifying the concepts concerning the understanding of violence, there is still no evidence that a better awareness of the concept of abuse has an effect on experiences of violence. Although no studies have demonstrated the relationship between the level of knowledge of violence and the probability of victimization, interventions such as those reported in these two selected studies are important because they improve elder people's knowledge of the subject and may influence the search for help in a situation of violence (39) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although three studies (31,(33)(34) carried out educational interventions that clarified what is considered violence to elder people and their families, modified and elucidated concepts and typologies, and two of them (31,34) showed results with statistical significance, with all participants in the intervention modifying the concepts concerning the understanding of violence, there is still no evidence that a better awareness of the concept of abuse has an effect on experiences of violence. Although no studies have demonstrated the relationship between the level of knowledge of violence and the probability of victimization, interventions such as those reported in these two selected studies are important because they improve elder people's knowledge of the subject and may influence the search for help in a situation of violence (39) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its focus on the elder person, the difficulty of this intervention involved the particularity of the scenario. Some of the challenges were the different conceptualizations of what consists elder abuse for the indigenous culture and the secular culture (39) , along with the social role of the elder person in the indigenous culture that influenced the success of this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Among a Native American sample, the prevalence of theft was followed by housing misuse and exploitative childcare demands placed on older Native Americans (Jervis et al 2017), actions perceived by older Native Americans as a form of resource sharing (or generosity) rather than financial exploitation (Gray 2017). Korean tradition stipulates that children respect and obey their parents, and in turn, as parents age sons are expected to willingly provide for their parents' physical, emotional, and financial well-being (Lee and Eaton 2009).The result of this tradition is that parents willingly share their income and savings with their children as if equal partners and therefore fail to perceive financial misuse as financial exploitation (Moon et al 2002).…”
Section: Intersectionality and Financial Abusementioning
confidence: 99%
“…Several members of the Native American community also view the increase in elder abuse among Native American populations resulting from the rejection of traditional tribal values and beliefs. Substance abuse and culture loss are also blamed for much of the elder mistreatment occurring in contemporary Native communities (Jervis et al, 2017). Other issues that often contribute to elder abuse in Native American communities include high unemployment, lack of economic opportunities, and high rates of substance abuse (Department of Health, and Human Services, Centers for Medicare, and Medicaid Services, 2015).…”
Section: Native Americansmentioning
confidence: 99%